Проблема нечіткої портфельної оптимізації та її вирішення із застосуванням методів прогнозування - Zaychenko, Yuri; Sydoruk, Inna (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2016)
The novel theory of investment portfolio optimization under uncertainty is presented based on fuzzy set theory and efficient forecasting methods. The direct problem of fuzzy portfolio optimization and dual problem are considered. In the direct problem structure of a portfolio is determined which provides the maximum profitableness at the given risk level. In dual problem the portfolio structure is determined which provides the minimum risk level at the set level of critical profitableness. For estimation of stocks profitableness in future moment the application of forecasting method- Fuzzy Group Method of Data Handling (FGMDH) is suggested. This method enables to construct fuzzy forecasting models by experimental data almost automatically. The experimental investigations of the suggested theory were carried out and comparison with classical portfolio model was performed.